Analisis Kondisi Aliran Fluida Dan Tekanan Di Sekitar Spar Dengan Sistem Redaman Lima Plat Vertikal - Dimas Fitrawan; Fuad Mahfud Assidiq (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
Spar type Floating wind Turbine is a floating structure that utilizes the speed of the sea wind to drive a turbine that can generate electrical energy .SPAR is a cylindrical floating structure that has a deep draft and is reliable in operating in the deep sea for a long time.in this study using a SPAR model with a damping system of five vertical plates located at the bottom of the SPAR structure where in this study the analysis about fluid flow conditions and pressures that are around the SPAR.this study was conducted by calculation numerical based CFD (Computational Fluid Dynamics) with four variations of fluid flow velocity used to observe changes in fluid flow conditions and pressure around the SPAR.this study aims to observe the conditions and influences around the SPAR type floating wind turbine structure which is expected to be a solution to energy problems in the world.